« Bizim PAOK » : réfugiés, sport et vénizélisme dans la Thessalonique de l’entre-deux-guerres - Lukas Tsiptsios (European Journal of Turkish Studies)
The historical object of the article is PAOK, a sports club founded in 1926 by Constantinopolitans in Thessaloniki. Through a prosopography of the founders and the directors, this essay aims at studying the paths taken and the means used by the Constantinopolitan elite to widely politicize the masses of refugees from Asia Minor, to enrol them durably in the Venizelist camp during the National Schism. In this way, a social history “from above” can be made, addressing sports as an answer to Thessaloniki’s social anomy in the Interwar Period, and the Venizelist political networks in Greece as a political elite among the refugees. Considering the club as a vector of ideological Venizelist speeches structuring a refugee identity, eventually allows us to highlight the construction of political antagonism through sports, between the locals and the refugees, and the mustering of antisemitism and violence by the elite of PAOK, in order to conquer the heart of Thessaloniki, in a procedure to gain a local and then a national hegemony.